STRATEGI KOMUNIKASI DALAM PENYULUHAN PERTANIAN DENGAN M VENDOR (SUATU PENDEKATAN KOMUNIKASI KELOMPOK & INTAPERSONAL) - EKO MURDIYANTO (Universitas Sebelas Maret, 2010)
Agricultural counseling process as a locomotive in spreading new technology to farmers has developed quickly since the introduction of several communication models, This quick development was also supported by development of counseling institutions and agricultural agents.